Low-temperature degradation increases the cyclic fatigue resistance of 3Y-TZP in bending. - Belli, Renan; Loher, Claudia; Petschelt, Anselm; Cicconi, Maria Rita; de Ligny, Dominique; Anglada, Marc; Lohbauer, Ulrich (Dental Materials, 2020)
OBJECTIVE: Due to past failures of orthopedic 3Y-TZP femoral implants linked to accelerated tetragonal-to-monoclinic phase transformation (t → m), the susceptibility to 'low-temperature degradation' or 'ageing' of 3Y-TZP has been advertised as detrimental to its long-term structural stability. However, no systematic mechanistic experiments on the fatigue resistance of aged 3Y-TZP under cyclic loading can support such statement. In this study, we aim to clarify this issue. METHODS: Here we evaluate the subcritical crack growth behavior of 3Y-TZP under cyclic loading after 0-50 h of accelerated ageing in an autoclave at 134 °C. The same 3Y-TZP sintered at two different temperatures (1450 °C or 1650 °C) allows for the comparison of materials containing grains with different susceptibilities to transformation. The volume fraction of surface transformed grains was measured using Raman spectroscopy, and the depth of the transformed surface layer from trenches milled with a Focus-Ion Beam. The fracture toughness before and after ageing was determined using the Chevron-notch Beam method. The quasi-static flexural strength was measured in dry conditions and the cyclic lifetime in water at 10 Hz and R-ratio = 0.3 in 4-point-bending at different applied stresses. The fatigue parameter n was derived from 3 different methods, namely SN curves, crack velocity plots and Weibull distributions. RESULTS: The progression of transformation showed linear kinetics with higher rates for the 3Y-TZP sintered at 1650 °C. Accelerated transformation induced severe crack formation within the transformed layer with parallel orientation to the surface plane, which supposedly behaved as the critical crack size population governing fracture. The stress intensity factor within the transformed layer was increased due to compressive stresses. Consequently, the fatigue parameter n increased consistently from 5 to 50 h of ageing, regardless of the derivation method, suggesting an increased resistance against crack growth during cyclic loading in bending. SIGNIFICANCE: Our results do not support the long suggested negative clinical implications of LTD regarding mechanical performance, to the contrary, LTD seems to increase the resistance against subcritical crack growth in a humid environment in bending.
EVALuna2:382963